Analisis Pengaruh Inflasi dan Pengangguran terhadap Tingkat Kemiskinan Pada Tahun 2018-2022 - Sitanggang, Dermawati; Ambarita, Grace Yosia; Fadly, Rizky (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
This study aims to analyze the effect of inflation and unemployment on the poverty rate in North Sumatra in 2018-2022. The data used in this study comes from the North Sumatra Province Central Bureau of Statistics and is a cross section or time series data. The model used in this research is a multiple linear regression model by testing autocorrelation, multicollinearity, normality, heteroscedasticity, F test, T test and coefficient determination test (R2). The estimation results show that inflation has a negative and significant effect on the poverty rate in North Sumatra province in 2018 - 2022. This means that if inflation increases, poverty in North Sumatra will decrease. The Unemployment variable has a negative and insignificant effect on Poverty in the province of North Sumatra in 2018 - 2022. Which means if unemployment increases it will reduce the poverty rate in North Sumatra